1985
DOI: 10.1093/bja/57.3.294
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Midazolam, Diazepam and Placebo I.M. As Premedication for Regional Anaesthesia

Abstract: In a randomized double-blind study, midazolam 0.1 mg kg-1 i.m. was compared with diazepam 0.2 mg kg-1 and placebo as premedication for patients undergoing urological interventions under spinal anaesthesia. The sedative and anxiolytic effects of midazolam were evident 5-10 min after administration, and were maximum between 30 and 90 min. After this, rapid recovery was observed. More than 90% of the patients receiving midazolam were totally or partially amnesic for the procedures in the induction room and the op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

1987
1987
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(14 citation statements)
references
References 3 publications
1
13
0
Order By: Relevance
“…[17] Several studies have compared the various routes of administration of midazolam and found that midazolam when administered intranasally produced a more rapid sedation than when administered through other routes. [114] However in another study by Lam et al ., intramuscular administration of midazolam produced better sedation and less movement at venipuncture than intranasal midazolam. [18] Lejus et al .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…[17] Several studies have compared the various routes of administration of midazolam and found that midazolam when administered intranasally produced a more rapid sedation than when administered through other routes. [114] However in another study by Lam et al ., intramuscular administration of midazolam produced better sedation and less movement at venipuncture than intranasal midazolam. [18] Lejus et al .…”
Section: Discussionmentioning
confidence: 97%
“…compared intramuscular midazolam with diazepam and placebo in patients undergoing urological interventions and reported that the former had a more rapid onset of sedation, produced a more profound sedation and amnesia than the other groups. [14] In another study comparing the effects of oral clonidine with oral midazolam in children undergoing tonsillectomy, the midazolam group fared better with lower anxiety scores on separation from parents and at induction, lesser postoperative pain scores and overall better satisfaction among parents with respect to the children's preoperative experience. [15] Singh et al .…”
Section: Discussionmentioning
confidence: 99%
“…However, it is reported that midazolam is quickly absorbed when intramuscularly injected and reaches a peak blood concentration 20-45 min after injection [11]. The sedative effect is said to appear clinically 5-10 min after injection [12], reach a peak at 30-40 rain, and to be maintained for about 60 min [3,6,13]. From these facts, if it is administered 60 min preoperatively, the peak effect is obtained before arriving in the operating room.…”
Section: Discussionmentioning
confidence: 99%
“…In addition several investigators reported little difference in anxiolytic effects between benzodiazepines and placebo. 6,7 We conducted a pilot, prospective, double-blind, randomized study to investigate the effect of benzodiazepine premedication on the stress response in patients undergoing daycase anesthesia and surgery. P Pa at ti ie en nt ts s a an nd d m me et th ho od ds s Sixty-one patients admitted for elective daycase surgery were enrolled into the study.…”
mentioning
confidence: 99%